Evaluation of the Achievement Improvement Training Program for Sepaktakraw Athletes - Padli; Tjung Hauw Sin; Yanuar Kiram; Jeki Haryanto; Ikhwanul Arifan; Muhammad Farid Al Abid (Universitas Pendidikan Ganesha, 2023)
The achievements of the Sepak Takraw branch have yet to show the achievements as expected, and several factors cause the inconsistent achievements. The success of athletes in achieving achievements must be connected to the training programs carried out by athletes. This study aims to analyze how athletes respond to the implementation of training programs to improve the achievement of athletes in the Sepaktakraw sport. The method used in this study is mixed. The sampling technique is a purposive sampling technique. The population used in this study were all takraw athletes, totaling 11 male athletes and 10 female athletes. The data collection instrument in this study was a takraw response questionnaire that would be given to athletes. Data analysis was carried out using descriptive analysis of the response questionnaire data given to the respondents. The research results are male athlete response data with an average of 75.00. The response given is very high. Based on the results of interviews conducted with the coaches of takraw athletes, it is known that the training programs carried out by athletes are systematically designed and carried out repeatedly to increase the athlete's ability to achieve achievements.